PRODUKSI TANAMAN CABE RAWIT (Capsicum frutescent L.) DI TANAH ULTISOL MENGGUNAKAN BOKASHI SAMPAH ORGANIK RUMAH TANGGA DAN NPK - Mega Silvia; Hilda Susanti; Samharinto Samharinto; Gt. Muhammad Sugian Noor (Universitas Lambung Mangkurat, 2016)
Research on the production of chilli in utisol soil using organic household waste bokashi and NPK was conducted in Banjarbaru from February to June 2015. The research used Completely Randomized Design (CRD) with six treatments. The treatments were (P1) 100% NPK, (P2) 100% NPK + bokashi, (P3) 75% NPK + bokashi, (P4) 50% NPK + bokashi, (P5) 25% NPK + bokashi, (P6) 100% bokashi. 100% NPK and 100% bokashi were 250 kg ha-1 NPK and 10 t ha-1 bokashi respectively. The result showed that the aplication of treatments gave affected to height increase, number of nodes, first day of appearing flower, biomass, fruit number and weight of fresh fruit The combination of 75% NPK and organic household waste bokashi can be recomended as the best doses for production of chilli. Organic household waste bokashi can contribute to reduce 25% of NPK aplication on the production of chili.